Oral Microbiome Analysis in Prospective Genome Cohort Studies of the Tohoku Medical Megabank Project - Saito, Sakae; Aoki, Yuichi; Tamahara, Toru; Goto, Maki; Matsui, Hiroyuki; Kawashima, Junko; Danjoh, Inaho; Hozawa, Atsushi; Kuriyama, Shinichi; Suzuki, Yoichi; Fuse, Nobuo; Kure, Shigeo; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
A baseline oral microbiome study of the Tohoku Medical Megabank Organization (ToMMo) was planned to characterize the profile of the oral microbiome in the Japanese population. The study also aimed to clarify risk factors for multifactorial diseases by integrated analysis of the oral microbiome and host genome/omics information. From 2013 to 2016, we collected three types of oral biospecimens, saliva, supragingival plaque, and tongue swab, from a total of 25,101 participants who had a dental examination in ToMMo. ToMMo has been strategically conducting two types of cohort studies. In this study, we used the Tohoku Medical Megabank (TMM) Community-Based Cohort Study (TMM CommCohort Study) and TMM Birth and Three-Generation Cohort Study (TMM BirThree Cohort Study) as discovery and validation cohorts, respectively, to select and identify microbial taxa related to oral diseases. We found through the 16S ribosomal RNA gene sequencing analysis of 834 participants of the TMM CommCohort Study that there are differences in the microbial composition and community structure between saliva and plaque. The species diversities in both saliva and plaque were increased in correlation with the severity of periodontal disease. These results were nicely reproduced in the analysis of 455 participants of the TMM BirThree Cohort Study. In addition, strong positive and negative associations of microbial taxa in both plaque and saliva with periodontitis-associated biofilm formation were detected by co-occurrence network analysis. The classes Actinobacteria and Bacilli, including oral health-associated bacterial species, showed a positive correlation in saliva, suggesting that saliva may play an important role in maintaining a healthy oral microbiome. These results revealed differences in microbial composition and community structure between saliva and plaque and a correlation between microbial species and the severity of periodontal disease. We expect that the large database of the oral microbiome in the TMM biobank will help in the discovery of novel targets for the treatment and prevention of oral diseases, as well as for the discovery of therapeutic and/or preventive targets of systemic diseases.